(untitled) (Latakia University Journal -Basic Sciences Series, 2020)
Fresh Melia Azdrecht flowers were extracted with absolute Ethanol for the first time in Syria, and then the contents of the extract were determined using technology of GC/MS. The percentage of extracted substances is 5% of the weight of the studied flowers. 39 compounds were identified in the extract. These compounds constitute 88.42% of the Ethanol extract. It is noted that the most important compounds discovered in the extract are: Glycyl-L-tryptophan (8.98%) ،Dicyclohexylhexanedioate (8.2%)، 3,17-Bis[(trimethylsilyl) oxy]androsta-3,5-diene (7.89%)، 5,6-Cyclopropa,3’,6-dihydro (3.beta.,5.beta.,6.alpha) cholestan-3-ol (6.23%)، N-methyl-1-[4-[2-(1piperidyl) ethoxy] phenyl] Propanamine ( 4.89%). It was also noted that there were other compounds with less appearance , the most important of them were: 2-ethyl-3-propyl Oxirane (4.31%)، 9-(1,2 dimethylpropyl) Borabicyclo[3.3.1]nonane (3.54%) ، bis(3-methylpheny l) 4-bromophenyl Phosphanoat (3.48%), N-methyl-1-(methylthio )-2-nitro Ethenamine (3.43%) and, 2,2’-dimethoxy-N-nitroso Diethylamine (3.25%). The toxicity influence of the extract was experimented on five types of plant fungi, where we discovered effective toxic Impact on them at all concentrations experimented: Rhizopus stolonifera (Rh.s), Alternaria citri (A.c), Fusarium oxysporum (F.o), Aspergillus niger (A.n), Alternaria citri (A.c) and Botrytis cinerea (B. C).